Evaluation Of The Shining Golden Gate Policy In Tabalong Regency, South Kalimantan (Case Study Evaluation Of Shining Gold Gate Performance Policy) (Journal of Pharmaceutical Negative Results, 2023)
Golden Gate is a regional development program of Tabalong Regency whose planning is in accordance with the mechanism of the national development planning system (SPPN) which is bottom up through Pramusrembang and Musrembang at the village, subdistrict and district levels. The objectives of this study are 1). Want to know and analyze the Performance of the Shining Golden Gate Policy in Tabalong District, 2). Want to know and analyze the Achievement of the Shining Golden Gate Program seen from the Human Development Index (HDI), 3). Want to know the Policy Model of the Shining Golden Gate in Tabalong District. The methods used in this study are qualitative research methods with case studies, the informants used are key, main and supporting informants, data collection by observation, interviews and documentation, with primary and secondary data sources, and data analysis in a qualitative way using the theory of Miles and Huberman (1992;16), namely data reduction, data presentation, drawing conclusions / verification. The results and discussion of the research are 1). The performance of the Shining Golden Gate Policy in Tabalong Regency has been going well in accordance with the objectives of the Shining Golden Gate Policy. 2) The achievement of the Shining Golden Gate Program in Tabalong Regency seen from the Human Development Index (IPM), is the Human Development Index (HDI) in Tabalong Regency has increased, which before the Shining Golden Gate Policy, Tabalong Regency for its HDI was still in 9th and 10th place in South Kalimantan, but after the Shining Golden Gate Policy, Tabalong Regency was included in 3rd place in South Kalimantan. 3) The Shining Golden Gate Policy Model in Tabalong Regency, is a Battom-up model, but the results show that the community really expects that the Bottom-up model implemented so far is not as pure as expected by the community, because the involvement of the Government is still very dominant both from its initiation and its facilitators. The Golden Gate, which is one of the policies in empowering the community, must have the involvement of the wider community, not just a few communities, including women from NGOs and the private sector are also involved and this must be truly stated in a clear commitment between all parties, including the government.